What moves the dead - Kingfisher, T. (Nightfire, a Tom Doherty Associates Book, 2022)
"From T. Kingfisher, the award-winning author of The Twisted Ones, comes What Moves the Dead, a gripping and atmospheric retelling of Edgar Allan Poe's classic "The Fall of the House of Usher." When Alex Easton, a retired soldier, receives word that their childhood friend Madeline Usher is dying, they race to the ancestral home of the Ushers in the remote countryside of Ruritania. What they find there is a nightmare of fungal growths and possessed wildlife, surrounding a dark, pulsing lake. Madeline sleepwalks and speaks in strange voices at night, and her brother Roderick is consumed with a mysterious malady of the nerves. Aided by a redoubtable British mycologist and a baffled American doctor, Alex must unravel the secret of the House of Usher before it consumes them all"--